One bad apple may not spoil the whole bunch: best friends and adolescent delinquency - Rees, Carter (Journal of quantitative criminology, 2011)
This study compared the association of adolescent delinquency with that of their best friend and remaining social network. Findings are reported from The National Longitudinal Study of Adolescent Health, a multi-wave nationally representative panel study of adolescents who were in grades 7–12 in 1994. Four delinquent outcomes were examined: Smoking, getting drunk, fighting, and a variety index of general delinquency. All analyses were replicated for three distinct criteria for identifying a “best friend.” We also examined several moderating factors and potential interrelationships between the best friend and remaining friendship group. Relative to the influence of the best friend, the influence of the remaining friendship group increased with group size, and with larger absolute disparities in delinquency levels between best and remaining friends. Our findings extend knowledge on the influence of best friends, and further underscore the importance of whether peer behaviors are measured directly (from the peers themselves) or indirectly (when focal respondents estimate the delinquent behavior of their peers).